New Isoquinoline Alkaloids from Paraphaeosphaeria sporulosa F03, a Fungal Endophyte Isolated from Paepalanthus planifolius - Amorim, Marcelo R. de [UNESP]; Paz, Tiago A. [UNESP]; Pinto, Luciano da S.; Hilario, Felipe [UNESP]; Zanini, Camila L.; Aguiar, Anna Caroline C.; Silva, Debora E. S. [UNESP]; Furlan, Maysa [UNESP]; Guido, Rafael V. C.; Bauab, Tais M. [UNESP]; Netto, Adelino V. de G. [UNESP]; Santos, Lourdes C. dos [UNESP] (Georg Thieme Verlag Kg, 2022)
As part of our continuing efforts to discover new bioactive compounds from endophytic fungal sources, we have investigated the extract of the Paraphaeosphaeria sporulosa F03 strain. The study led to the isolation of four new 3-methyl-isoquinoline alkaloids ( 1 - 4 ) and four known polyketides ( 5 - 8 ). The structures of compounds 1 - 4 were elucidated by 1D and 2D NMR experiments and HRMS analysis. The absolute configuration of 4 was determined by comparison of its experimental electronic circular dichroism spectrum with calculated data. Compounds 1 - 4 exhibited antifungal activity with minimal inhibitory concentration values ranging from 6.25 - 50 mu g/mL against six Candida species but they did not present any cytotoxic activity against the human tumor cell lines A549 (lung), MCF-7 (breast), and HepG2 (hepatocellular). In addition, compound 4 exhibited antiplasmodial activity in the low micromolar range (IC (50) = 4 mu M).
Keywords: Isoquinoline; Endophytic fungus; Paraphaeosphaeria sporulosa; Paepalanthus planifolius; Eriocaulaceae